Transportation Costs, Increasing Returns and Regional Growth: An Interregional CGE Analysis - Eduardo Haddad; Geoffrey Hewings (European Regional Science Association (ERSA), 2004)
The purpose of this paper was threefold. First, we presented a flexible analytical framework, based on sound and consistent economic theory and data, in order to assess the likely state/sectoral/income effects of policy changes in Brazil. This is the first fully operational interstate CGE model implemented for the Brazilian economy, based on previous work by the author and associates. Among the features embedded in this framework, modeling of scale economies and transportation costs provides an innovative way of dealing explicitly with theoretical issues related to integrated regional systems. Results seemed to reinforce the need to better specifying spatial interactions in interregional CGE models. Second, in order to illustrate the analytical capability of the CGE module, we presented a simulation, which evaluated the regional impacts of a decrease in transportation costs, in accordance with recent policy developments in Brazil. Rather than providing a critical evaluation of this debate, we intended to emphasize the likely structural impacts of such policies. Third, previous diagnostics suggested the need to make a more in-depth analysis of trade flows between the Brazilian states, potentially leading to generalizations regarding the type of trade involved, changes in its composition through time as the Brazilian economy develops, and the implications of these structural differences in the coordination and implementation of development policies. In order to address this issue we gave interregional trade its proper place by taking into account a fully specified interstate system of accounts specially developed for the purpose of calibrating the CGE model.
Keywords: 330